Assessment Internalisasi Nilai-Nilai Pancasila pada Program Penguatan Pendidikan Karakter (PPK) di SMPN 4 Palimanan Kabupaten Cirebon - Aissa, Siti; Winarso, Widodo; Wijaya, Apriyanda Kusuma (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2022)
The role of schools is considered very important in strengthening character education, unfortunately not all schools are successful in implementing character education strengthening programs (PPK) in accordance with the noble values of the Indonesian nation. This study aims to find out and examine more deeply about the internalization of Pancasila values in the PPK program at SMPN 4 Palimanan. By using the type of assessment research through a qualitative approach, and the combination of the CIPP model with authentic assessment. Using collection techniques, including observation and documentation by checking the validity of triangulation data techniques and sources. And through several stages of analysis, namely reduction, presentation of data and conclusions. The results of this study show that the success of the PPK program based on the assessment context can be seen in the success of the school vision and mission, school regulations, and school culture/climate in its implementation at SMPN 4 Palimanan and the internalization of Pancasila values in the PPK program have all been well internalized.